Ethical issues on tax evasion from the students' perception - Ismail, Ida suriya; Suman, Siti Aida; Noor Hasnizam, Puteri Adlina; Shaharin, Nurul Najihah; Rusnipa, Hanis Aqilah (UiTM Cawangan Johor, 2022)
Paying taxes is not a favorable choice; even it is a compulsory financial obligation to each taxpayer towards its government. However, the evasion of ta7' is immoral since it is illegal and unethical. This paper examines university students' perception in Malaysia on the ethics of tax evasion. A survey method consisting of 18 statements was distributed to 120 students from Diploma to Postgraduate students in three higher learning institutions. This study used descriptive analysis to examine the overall mean responses and followed by additional analysis to compare the mean responses according to the respondents age and level of educations. The results of this study indicated that respondents agreed that ta7' evasion was unethical. However, tax evasion becomes ethical under some circumstances when the tax system is unfair and the government or political party is involved in corruption. In terms of age, the youngest group (18 - 25 years old) tends to believe that tax evasion was ethical compared to medium age and older age groups. Besides, the diploma students felt that tax evasion was ethical when they had the highest score than students with degree and masters level. The findings show an early indicator of future taxpayers who believe that ta7' evasion is ethical depending on the governments governance, taxpayers experience, and the level of tax knowledge. Therefore, this study recommends universities to educate their students on tax evasion areas through the formal syllabus or informal programs in ensuring their students to become good taxpayers.